The diabetes pandemic and associated infections: suggestions for clinical microbiology. Issue 1 (January 2019) - Toniolo, Antonio; Cassani, Gianluca; Puggioni, Anna; Rossi, Agostino; Colombo, Alberto; Onodera, Takashi; Ferrannini, Ele
Abstract : N/A: There are 425 million people with diabetes mellitus in the world. By 2045, this figure will grow to over 600 million. Diabetes mellitus is classified among noncommunicable diseases. Evidence points to a key role of microbes in diabetes mellitus, both as infectious agents associated with the diabetic status and as possible causative factors of diabetes mellitus. This review takes into account the different forms of diabetes mellitus, the genetic determinants that predispose to type 1 and type 2 diabetes mellitus (especially those with possible immunologic impact), the immune dysfunctions that have been documented in diabetes mellitus. Common infections occurring more frequently in diabetic vs. nondiabetic individuals are reviewed. Infectious agents that are suspected of playing an etiologic/triggering role in diabetes mellitus are presented, with emphasis on enteroviruses, the hygiene hypothesis, and the environment. Among biological agents possibly linked to diabetes mellitus, the gut microbiome, hepatitis C virus, and prion-like protein aggregates are discussed. Finally, preventive vaccines recommended in the management of diabetic patients are considered, including the bacillus calmette-Guerin vaccine that is being tested for type 1 diabetes mellitus. Evidence supports the notion that attenuation of immune defenses (both congenital and secondary to metabolic disturbances as well as to microangiopathy and neuropathy) makes diabetic people more prone to certain infections. Attentive microbiologic monitoring of diabetic patients is thus recommendable. As genetic predisposition cannot be changed, research needs to identify the biological agents that may have an etiologic role in diabetes mellitus, and to envisage curative and preventive ways to limit the diabetes pandemic.